Clinicopathological evaluation of the terminal end of the distal rectal pouch and fistula site in anorectal malformation - Kushwaha, Renu; Kushwaha, Santosh; Singh, Nirbhay; Saxena, Rakesh; Mitra, Shaila; Mathur, Sujeet Kumar (International Surgery Journal, 2024)
Background: The aim is to assess the clinicopathological evaluation of the terminal end of the distal rectal pouch and fistula site in anorectal malformation (ARM). Methods: This study was conducted on patients who attended the surgery OPD and included 40 cases of ARMs over a 12-month period. All cases were admitted to the department of surgery at B. R. D. medical college, Gorakhpur, UP. Results: Out of 40 cases studied 22 cases (55%) were female and 18 cases (45%). Out of total 40 cases, recto-bulbourethral fistula shown by 8 male patient (20%), recto-prostatic fistula shown by 8 male patient (20%), and recto-bladder neck fistula shown by 2 male patient (5%) out of total 18 male patient (45%) of total cases. Recto-vestibular fistula shown by 7 female patient (17.5%), ano-vestibular fistula by 11 male patient (27.5%), low rectovaginal fistula shown 3 female patient (7.5%), and no fistula shown by 1 female patient (2.5%) out of total 22 female patient (55%). In our study wound infection (5 cases) 12.5%, excoriation (5 cases) 12.5 %, constipation and bleeding (2 case) 5% were noted, no complication seen in 65% cases. All of them were treated conservatively followed by anal dilatation. Conclusions: Histopathological variations in the distal rectal pouch and fistula site of ARMs have led to differing opinions on whether to preserve or excise the fistula site. Our study found that 45% of patients had a smooth muscle layer present in the histopathological examination.